On the nature of basic human needs: The desire for self-consistency versus self-growth. - Tuson, Kim M. (University of Ottawa (Canada), 1995)
Swann's (1983, 1987, 1990) self-verification theory assumes that people are invested in preserving a stable and unchanging sense of self, and that they do so by interacting with others who treat them in a manner consistent with their sense of self. Deci and Ryan's (1985, 1987, 1991) self-determination theory assumes that people are intrinsically oriented towards seeking growth and progressive change in their sense of self, and that it is by interacting with others who support their autonomy that these growth strivings are best satisfied. Two pilot studies and three full-scale studies tested (a) whether self-consistency versus self-growth needs govern people's preferences for who they interact with, and (b) the kinds of consequences that ensue from such interactions. Globally, we hypothesized that if Swann's self-verification theory holds true, self-determined individuals will prefer to interact with others who are also self-determined in their motivation, and who are autonomy-supportive in their interpersonal style. Nonself-determined individuals, on the other hand, will prefer interactions with others who are nonself-determined in their motivation, and rather directive and controlling in their interpersonal style. By contrast, we anticipated that if Deci and Ryan's self-determination theory holds true, all persons, regardless of their motivational orientation, will prefer to interact with others who are relatively self-determined in their motivation and autonomy-supportive in their interpersonal style. In line with Swann's self-verification theory, results of Pilot Study 2, Study 2, and Study 3 indicated that subjects preferred to interact with others who were similar to themselves. Specifically, when we examined the similarity between university students and their two closest university friends in terms of their motivation for attending school, findings indicated that self-determined students preferred to associate with friends who were significantly more self-determined than the friends of nonself-determined students (Pilot Study 2, Study 2). Similarly, when we examined married and common-law couples' motivation for being involved in their relationship, a significant correlation emerged between their motivational orientations (Study 3). In both cases, the pattern of results held up whether we considered actual motivation similarity or perceived motivation similarity between subjects and their relationship partners. Despite the fact that subjects chose to affiliate with others similar to themselves, results of Pilot Study 1, Study 1, and Study 3, revealed that such types of interactions were not the kind that subjects would prefer to have, nor the kind that were associated with superior relationship outcomes. In line with Deci and Ryan's self-determination theory, when students were presented with descriptions of two types of teaching styles--one autonomy-supportive, the other directive and controlling--students of both motivational orientations indicated a clear preference for the autonomy-supportive teaching style (Pilot Study 1, Study 1). When asked which of the two teaching styles they considered to be more effective, students again judged the autonomy-supportive teaching style to be superior (Study 1). Finally, when couples were asked to rate the quality of their relationship, they reported greater adaptiveness in their couple behaviors, more commitment towards their relationship, and higher levels of happiness within their relationship to the extent that their motivation towards the relationship was self-determined and that their partner was perceived to be autonomy-supportive (Study 3). Results are discussed in terms of reconciling this apparent difference between what people seem to want (self-growth) and what people seem to do (self-consistency).
Keywords: Psychology, Social.